EFFECT OF AIR JET COOLING ON SURFACE ROUGHNESS AND TOOL WEAR - Paryanto Rusnaldy dan Tony S. Utomo (Universitas Gadjah Mada, 2012)
The main goal of this work is to investigate the use of air jet cooling on machining process. Surface roughnessand tool are chosen as parameter to analyze of air jet cooling effects; and turning process with AISI 1010 materialused in the experimental study. Surface roughness was measured for several air jet pressures and in two air jetpositions. Every five minutes of machining time, tool wear was measured until reach 30 minutes. Initial resultsshow that the use of air jet cooling with proper selection of position and pressure; possible to reduce tool wear andto increase surface roughness.